Access to information about the activities of the Security Service of Ukraine in the context of countering disinformation - A. I. Marushchak; N. O. Kudriavtseva (Bulletin of Kharkiv National University of Internal Affairs)
Rapid globalization and informatization of everyday processes, mass use of Internet resources and social networks contribute to the uncontrolled spread of disinformation. A general analysis of the concept of disinformation was carried out, its various interpretations were considered, and it was highlighted in broad and narrow understandings. The measures implemented by Ukraine to combat this dangerous phenomenon are outlined. Separate characteristics of the concept of “disinformation” are provided.